Effects of macrophages in OSCC progression - Dong, Xiaodan; Dong, Chunling; Li, Bo (Frontiers in Immunology, 2025)
Macrophages are crucial immune cells within the tumor microenvironment (TME), involved in regulating tumor proliferation, invasion, metastasis, ECM remodeling, angiogenesis, and immunosuppression. Although more and more experimental evidence and clinical data indicate that macrophages are involved in the onset and progression of oral squamous cell carcinoma (OSCC), the exact pathogenesis of OSCC associated with macrophages has not been fully elucidated. Enhanced knowledge of the molecular mechanisms involving macrophages in OSCC will aid in the creation of treatments targeted specifically at macrophages. This review outlines the pro-tumoral and anti-tumoral effects of macrophages in OSCC, emphasizing the interaction between OSCC cells and macrophages. It can provide theoretical basis for the establishment of complex regulatory network centered on macrophages and explore novel therapeutic strategies for OSCC.